2019
DOI: 10.1080/19942060.2018.1562383
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a CFD based optimization procedure for the design of torque converter cascade

Abstract: Traditional one-dimensional (1D) design theory no longer satisfies modern torque converter design requirements due to the lack of accuracy and long trial-and-error process. A computational fluid dynamics (CFD) based optimization approach was brought forward. This study is devoted to two key processes in bringing CFD into torque converter design -blade parameterization/evaluation and optimization. A six-parameter blade camber line design method was employed to represent the blade shape. The blade profile was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…2,3 Traditional researchers have carried out work on the cascade system of TC, including the design of parameters such as blade shape, 4 number, and angle. [5][6][7] Liu et al 8 discussed the parameter sensitivity of blade using multi-objective genetic algorithm and found that the shape parameters of blade, namely the inlet and outlet angle, and camber peak value, are vital to the performance. However, previous research work has focused on the key design parameters of blade profiles to reduce pressure loss and impact loss.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Traditional researchers have carried out work on the cascade system of TC, including the design of parameters such as blade shape, 4 number, and angle. [5][6][7] Liu et al 8 discussed the parameter sensitivity of blade using multi-objective genetic algorithm and found that the shape parameters of blade, namely the inlet and outlet angle, and camber peak value, are vital to the performance. However, previous research work has focused on the key design parameters of blade profiles to reduce pressure loss and impact loss.…”
Section: Introductionmentioning
confidence: 99%
“…The flow structure demonstrated that the instantaneous flow status of each blade was not identical, indicating that a simulation-based on periodic boundaries of a single passage has certain limitations for these devices. An important component of automatic transmissions (Liu et al, 2018b), HTC is comprised of three elements:…”
Section: Numerical Simulationmentioning
confidence: 99%
“…The HTC is crucial for whole vehicles due to its ability of torque multiplication, automatic adaptability and shock absorption (Li et al, 2019;You et al, 2018). Nonetheless, the fluid in the working chamber of HTC is driven by the rotating rotor and restricted by the blade wall, which leads to the rotation effect of the flow, and further complicates the development of turbulence (Liu et al, 2019(Liu et al, , 2018b. The prediction of dynamic performance and economics performance remains as a major challenge for the design.…”
Section: Introductionmentioning
confidence: 99%
“…This approach adopts the sample points selected by the orthogonal array design (OAD), and its spatial filling and equalization are not as good as the optimal Latin hypercube design (Opt LHD), so the error of prediction calculation is larger. 15 Liu et al 16,17 proposed a multi-objective optimization problem with the stall pump capacity factor λ B 0 and the K 0 as the objective function and 19 blade shape parameters as the independent variables. The Kriging method has great advantages in terms of accuracy and efficiency compared to the response surface methodology (RSM).…”
Section: Introductionmentioning
confidence: 99%